2022
DOI: 10.3390/ijerph19127350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankle Weights as a Frailty Prevention Strategy in the Community-Dwelling Elderly: A Preliminary Report

Abstract: Since the start of the COVID-19 pandemic, many healthy older adults have been less willing to engage in group exercise for fear of contracting this illness. Therefore, there is a need for an effective home-based exercise program to prevent frailty in the elderly. In this study, we assessed the effectiveness of ankle weights as a frailty prevention device for older adults. The study participants were aged 50–90 years and were screened for falls using the Motor Fitness Scale. Participants were divided into two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, ankle weights (AWs) were used instead of HHWs, as the AVRGs connected with the omnidirectional treadmill primarily engaged the lower limbs. It should be emphasized that AWs are sports equipment used in jogging, fitness, rehabilitation, etc., and wearing AWs can help improve gait, lower limb strength, and balance [24][25][26]. Although AWs are commonly used in training, there is a lack of research into their impact on improving the effectiveness of exercises in VR.…”
Section: Introductionmentioning
confidence: 99%
“…However, ankle weights (AWs) were used instead of HHWs, as the AVRGs connected with the omnidirectional treadmill primarily engaged the lower limbs. It should be emphasized that AWs are sports equipment used in jogging, fitness, rehabilitation, etc., and wearing AWs can help improve gait, lower limb strength, and balance [24][25][26]. Although AWs are commonly used in training, there is a lack of research into their impact on improving the effectiveness of exercises in VR.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent training interventions that lasted three months and were performed three times per week for one hour per session or lasted longer duration (≥ 5 months) and were performed three times per week for 30-45 min per session had a positive impact on frail older adults [50]. Previous studies revealed the home-based frailty prevention program is feasible and help prevent frailty [51][52][53]. The exercise training in the present study, including resistance training, balance training, and stretching exercises, which is safe, easy to learn, without taking up space, and suitable for doing at home.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the muscle strength of the lower limbs, we employed the 30 s chair stand test (CS-30), which does not require a measuring device and is commonly used in clinical practice. The CS-30 measures the number of times a person can stand up in 30 s from a chair approximately 40 cm in height [ 23 ]. If the 30 s ended while the participant was in the process of standing up, this was counted as one time if the torso and knees were already extended.…”
Section: Methodsmentioning
confidence: 99%